Red Wine and Health: Approaches to Improve the Phenolic Content During Winemaking - Vejarano, Ricardo; Luján-Corro, Mariano (Frontiers in Nutrition, 2022)
There is ample evidence regarding the health benefits of red wine consumption due to its content of phenolic compounds, as an alternative to improve the state of health and prevent various diseases, being the implementation of procedures that allow a greater extraction and stability of phenolic compounds during the elaboration a key aspect. The first part of this review summarizes some studies, mostly at the preclinical level, on the mechanisms by which phenolic compounds act in the human organism, taking advantage of their antioxidant, anti-inflammatory, antitumor, antithrombotic, antiatherogenic, antimicrobial, antiviral, and other activities. Although the migration of grape components into the must/wine occurs during the winemaking process, the application of new technologies may contribute to increasing the content of phenolic compounds in the finished wine. Some of these technologies have been evaluated on an industrial scale, and in some cases, they have been included in the International Code of Oenological Practice by the International Organization of Vine and Wine (OIV). In this sense, the second part of this review deals with the use of these novel technologies that can increase, or at least maintain, the polyphenol content. For example, in the pre-fermentative stage, phenolic extraction can be increased by treating the berries or must with high pressures, pulsed electric fields (PEF), ultrasound (US), e-beam radiation or ozone. At fermentative level, yeasts with high production of pyranoanthocyanins and/or their precursor molecules, low polyphenol absorption, and low anthocyanin-β-glucosidase activity can be used. Whereas, at the post-fermentative level, ageing-on-lees (AOL) can contribute to maintaining polyphenol levels, and therefore transmitting health benefits to the consumer.